Efficacy of ixazomib-lenalidomide-dexamethasone in high-molecular-risk relapsed/refractory multiple myeloma – case series and literature review - Aneta Szudy-Szczyrek; Sylwia Chocholska; Oliwia Bachanek-Mitura; Olga Czabak; Radosław Mlak; Michał Szczyrek; Justyna Muzyka-Kasietczuk; Marek Hus (Annals of Agricultural and Environmental Medicine, 2021)
Introduction and objective Multiple myeloma (MM) is an incurable condition with variable clinical course. The study included a group of patients with especially poor-prognosis, individuals with relapsed/refractory multiple myeloma (RRMM) and specific cytogenetic disorders. Among the currently used therapies the ixazomib-lenalidomid-dexamethasone (IRd) is considered as a candidate to improve outcomes. The aim of the study was to evaluate the safety and efficacy of IRd regimen in the treatment of patients with RMMM.